Wear-resistant dual-purpose ceramic glaze and preparation method thereof

Through the combination of modified white corundum and nano-silica materials, the problem of insufficient wear resistance of traditional ceramic glaze is solved, and the high hardness and high temperature resistance of ceramic glaze is achieved, which extends the service life and improves the aesthetics.

CN119118510AActive Publication Date: 2024-12-13FOSHAN TAOYING NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411247421.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The wear resistance of traditional ceramic glaze is limited and it is difficult to meet higher usage needs.

Method used

By modifying the combination of materials such as white corundum and nano-silica, the hardness and wear resistance of the glaze are improved by using silane coupling agent modification and doping technology, and a wear-resistant coating is sprayed on the surface of the ceramic glaze to form a high hardness , high temperature resistant ceramic glaze.

Benefits of technology

It significantly improves the wear resistance and service life of ceramic products, while improving the gloss and aesthetics of the glaze, enhancing the overall performance of the glaze.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to wear-resistant dual-purpose ceramic glaze and a preparation method thereof, and belongs to the technical field of ceramic preparation. According to the invention, the white corundum is modified, the silane coupling agent is firstly used for surface modification, then the doped composite metal is used for structural modification, and the modified white corundum has higher hardness and wear resistance and can effectively resist wear and scratches, so that the service life of a ceramic product is prolonged; the modified white corundum can also enable the glaze surface to be finer, smoother and glossy, so that the appearance quality of the ceramic product is improved; according to the method, the wear-resistant coating is added on the surface of the ceramic glaze by spraying, and the coating with extremely strong binding force can be formed on the surface of the ceramic glaze due to the fact that a coating material can permeate into tiny pores of the ceramic glaze in the spraying process, so that the coating is not easy to peel off, and the service life of the coating is prolonged. According to the coating, the wear resistance is improved, and meanwhile, the overall attractiveness of the ceramic glaze is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic preparation, and relates to a wear-resistant dual-purpose ceramic glaze and a preparation method thereof. Background Art

[0002] Glaze is a silicate. The glaze applied on ceramics is generally made of quartz, feldspar, and clay. After grinding and adding water, it is applied to the surface of the body and melted after being fired at a certain temperature. When the temperature drops, a thin glassy layer is formed on the surface of the ceramic. There are many types of glazes. According to the body, they can be divided into: porcelain glaze, pottery glaze and flint glaze; according to the firing temperature, they can be divided into: high-temperature glaze and low-temperature glaze; according to the appearance characteristics, they can be divided into: transparent glaze, opalescent glaze, color glaze, glossy glaze, matte glaze, crackle glaze (opening), crystal glaze, etc.; according to the composition of the glaze, they can be divided into: lime glaze, feldspar glaze, lead glaze, lead-free glaze, boron glaze, lead-boron glaze, etc. Ceramic glazing refers to attaching a layer of glassy material on the surface of the ceramic body by high temperature. The purpose of glazing is to improve the surface physical and chemical properties of the body, while increasing the beauty of the product and improving the performance of the product. Glazing methods can be divided into wet glazing and dry glazing. Common ones include dipping glaze, pouring glaze, spraying glaze, brushing glaze, and vaporization glazing.

[0003] In traditional technology, the hardness and wear resistance of the glaze are generally improved by adding wear-resistant media, but the improvement in wear resistance is limited. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant dual-purpose ceramic glaze and a preparation method thereof, which has the characteristics of wear resistance and stain resistance.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The preparation method of the wear-resistant dual-purpose ceramic glaze is specifically as follows:

[0007] S1: Put the glaze ingredients into a ball mill according to the formula ratio, the speed of the ball mill is 300r / min, after grinding for 1h, add 20wt% of water, 10wt% of ethylene glycol, 0.5wt% of calcium oxide and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain glaze E;

[0008] The formula of the glaze composition is as follows by mass percentage: modified white corundum 25-30%, quartz 20-25%, petalite 20-25%, kaolin 10-15%, silicon carbide 10-15%, and boron carbide 5-10%;

[0009] The preparation method of modified white corundum is as follows:

[0010] S1.1: Mix chromium nitrate and nano-titanium dioxide in a mass ratio of (1-3):1, put them into a ball mill for grinding, the ball mill speed is 300r / min, the grinding time is 0.5h, and a mixture A is obtained;

[0011] S1.2: calcining the mixture A at 300-400°C for 2-3h to obtain a composite oxide B, mixing the composite oxide B and white corundum in a mass ratio of 1:(2-4), adding 0.2wt% of rare earth oxide and 0.1wt% of polyethylene glycol 2000, and grinding in a ball mill at a speed of 300r / min for 0.5h to obtain a mixture C;

[0012] S1.3: Use a 10% alkali solution at room temperature to wash the mixture C, then immerse the washed mixture in a silane coupling agent, stir at a speed of 150 r / min, and heat to 60°C at a rate of 3°C / min while stirring. After keeping the temperature constant for 1 hour, put it in a 110°C oven and dry it for 12 hours to obtain a mixture D;

[0013] S1.4: The mixture D is transferred to 2000° C. for sintering for 1 hour, and then ground to a particle size of 150 mesh after cooling to room temperature to obtain the modified white corundum;

[0014] S2: The surface of the green body is purged with nitrogen, and glaze E is poured on the surface of the green body by a pouring glaze method. After the pouring glaze is completed, the green body is left to dry to obtain a green body F;

[0015] S3: placing the green body F in a kiln for firing at a kiln temperature of 2200°C and a firing cycle of 70 minutes, cooling to room temperature after firing, and polishing to obtain green body G;

[0016] S4: spraying a layer of wear-resistant coating on the surface of the body G to obtain the wear-resistant dual-purpose ceramic glaze.

[0017] Furthermore, the rare earth oxide in S1.2 is one or more of cerium oxide, lanthanum oxide, and praseodymium oxide.

[0018] Furthermore, the alkaline solution in S1.3 is one of aqueous ammonia, sodium hydroxide solution and potassium hydroxide solution.

[0019] Furthermore, the silane coupling agent in S1.3 is one of silane coupling agent KH-560 and silane coupling agent KH-792.

[0020] Furthermore, the flow rate of nitrogen in S2 is 10 m / s.

[0021] Furthermore, the parameters of the glazing method in S2 are: pouring distance 35 cm, glazing amount 60 g / piece, and tile size 300*600 mm.

[0022] Furthermore, the polishing parameters in S3 are: first, polishing with a 500-mesh grinding head for 0.5 h, then polishing with a 1000-mesh grinding head for 0.5 h, and finally polishing with a 2000-mesh grinding head for 1 h.

[0023] Furthermore, the preparation method of the coating used for the S4 wear-resistant coating is as follows: dissolving fluorosilicone resin in isopropyl acetate to obtain a mixed solution with a mass fraction of 60%, adding 0.5wt% nano-silicon dioxide, and grinding at a speed of 400r / min for 2h to obtain the coating used for the wear-resistant coating.

[0024] Furthermore, the parameters of the S4 spraying are a spraying distance of 60 mm and a spraying rate of 50 mm / s.

[0025] White corundum, also known as alumina, is a synthetic material with alumina as the main component. It has the characteristics of high hardness, high wear resistance, high heat resistance, good chemical stability and corrosion resistance. Through modification, the hardness and wear resistance of the glaze surface can be further improved to meet more use conditions. The white corundum in the present invention is purchased from Wuhan Jiyesheng Chemical Co., Ltd. with a purity of 99%.

[0026] During the surface modification process, the white corundum is first treated with alkali washing to remove surface impurities and increase the hydroxyl content, and then modified with a silane coupling agent. The silane coupling agent can react with the hydroxyl groups on the surface of the white corundum to make its surface organic, thereby enhancing its solubility and binding force with organic matter. The use of the silane coupling agent can also enhance the binding force between the glaze layer and the substrate, while improving the glossiness of the glaze surface, making it more ornamental.

[0027] The doping of metal elements can change the crystal structure and electronic state of white corundum, thereby improving its performance. The hardness and wear resistance of white corundum can be improved by doping with chromium elements. Chromium elements can be partially dissolved in the crystal lattice of white corundum to form a solid solution. This solid solution will cause lattice distortion and increase dislocation density, thereby hindering dislocation movement and improving the hardness and strength of the material. At the same time, the solid solution can also improve the wear resistance of the material, because the obstruction of dislocation movement makes the surface of the material more difficult to wear. Insoluble chromium elements will form second-phase particles in white corundum. These second-phase particles can act as hard points and play a supporting role when the material is worn, reducing the amount of wear of the material. In addition, the second-phase particles can also hinder the expansion of cracks and improve the fracture toughness of the material.

[0028] Titanium can react with oxygen in white corundum to form high-melting-point titanate compounds. These high-melting-point compounds can still maintain a stable structure at high temperatures, thereby improving the material's high-temperature resistance; titanium doping can also change the thermal expansion coefficient and thermal conductivity of white corundum and other thermal physical properties, making it have better thermal stability at high temperatures, which helps reduce thermal stress and thermal fatigue damage of the material at high temperatures.

[0029] The doping of rare earth oxides can improve the wear resistance of the material by refining the grains and reducing defects. The white corundum and the doped composite metal are then sintered at high temperature to improve their overall strength. The use of modified white corundum as the material makes the ceramic glaze have better wear resistance.

[0030] In order to further improve the wear resistance and aesthetics of ceramic glaze, a wear-resistant coating is attached to the surface of the ceramic glaze. Fluorosilicone resin itself has excellent wear resistance, and the addition of nano-silicon dioxide further enhances the hardness and wear resistance of the coating. Nano-silicon dioxide has the surface effect and small size effect of nano-materials, and can form a uniform dispersed phase in the coating, enhance the density and hardness of the coating, and thus resist external wear; the interfacial force between nano-silicon dioxide and fluorosilicone resin is strong, and can form a stable bond to prevent the coating from peeling off during wear, and the fluorine atoms in fluorosilicone resin have low surface energy, which can form a lubricating film on the surface of the coating to reduce friction and wear; in addition, the fluorosilicone resin coating has a smooth and flat surface, which can enhance the overall aesthetics of the ceramic glaze, and the addition of nano-silicon dioxide can further enhance the glossiness of the coating and enhance the aesthetics.

[0031] During the curing process, the curing of the fluorosilicone resin coating is a cross-linking reaction process, and a three-dimensional network structure is formed through the chemical reaction between the resin molecules. Nano-silicon dioxide can be fixed in the coating as an inorganic filler to form a stable combination with the resin molecules. The fluorosilicone resin of the present invention is purchased from Hubei Zhonglong Kangsheng Fine Chemical Co., Ltd. with a purity of 99%;

[0032] In the formula of the present invention, the hardness and chemical stability of quartz make it not easily damaged under wear and high temperature environment, and its anti-colorization performance helps to maintain the beauty of the glaze; the hardness and wear resistance of lithium feldspar improve the overall hardness and wear resistance of the glaze through physical filling and reinforcement; the chemical stability and reinforcement of kaolin enable the glaze to maintain good performance when it is worn and chemically eroded; the high hardness and wear resistance of silicon carbide and boron carbide resist wear and erosion through physical barrier effect, and their high temperature resistance ensures the stable performance of the glaze in high temperature environment.

[0033] Beneficial effects of the present invention:

[0034] The present invention modifies white corundum by first performing surface modification with a silane coupling agent and then performing structural modification by doping with a composite metal. The modified white corundum has higher hardness and wear resistance, can effectively resist wear and scratches, thereby extending the service life of ceramic products. The modified white corundum can also make the glaze surface more delicate, smooth and glossy, thereby improving the appearance quality of ceramic products.

[0035] The present invention adds a wear-resistant coating on the surface of the ceramic glaze by spraying. This method can form a coating with extremely strong bonding force on the surface of the ceramic glaze. This is because during the spraying process, the coating material can penetrate into the tiny pores of the ceramic glaze, making the coating less likely to peel off. The coating improves the overall aesthetics of the ceramic glaze while improving the wear resistance. DETAILED DESCRIPTION

[0036] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0037] Formula ratio 1: by mass percentage, modified white corundum 30%, quartz 20%, petalite 20%, kaolin 10%, silicon carbide 10%, boron carbide 10%;

[0038] Formula ratio 2: by mass percentage, modified white corundum 25%, quartz 25%, petalite 20%, kaolin 10%, silicon carbide 10%, boron carbide 10%;

[0039] Formula ratio 3: by mass percentage, modified white corundum 25%, quartz 20%, petalite 25%, kaolin 15%, silicon carbide 10%, boron carbide 5%;

[0040] Formula ratio 4: by mass percentage, modified white corundum 30%, quartz 20%, petalite 20%, kaolin 10%, silicon carbide 15%, boron carbide 5%;

[0041] Example 1

[0042] The preparation method of the ceramic glaze in this embodiment is as follows:

[0043] S1: Put the ingredients of the glaze into a ball mill according to the formula ratio 1, the speed of the ball mill is 300r / min, after grinding for 1h, add 20wt% of water, 10wt% of ethylene glycol, 0.5wt% of calcium oxide and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, and use a magnetic iron remover to remove iron to obtain glaze E;

[0044] The preparation method of modified white corundum in this embodiment is as follows:

[0045] S1.1: Mix chromium nitrate and nano-titanium dioxide in a mass ratio of 2:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 0.5 h, and a mixture A is obtained;

[0046] S1.2: calcining mixture A at 300°C for 2h to obtain composite oxide B, mixing composite oxide B and white corundum in a mass ratio of 1:4, adding 0.2wt% of cerium oxide and 0.1wt% of polyethylene glycol 2000, and grinding in a ball mill at a speed of 300r / min for 0.5h to obtain mixture C;

[0047] S1.3: Use 10% ammonia water at room temperature to perform alkali washing on the mixture C, then immerse the mixture after alkali washing in silane coupling agent KH-560, stir at a speed of 150 r / min, and heat to 60°C at a rate of 3°C / min while stirring. After keeping the temperature constant for 1 hour, put it in an oven at 110°C and dry it for 12 hours to obtain a mixture D;

[0048] S1.4: The mixture D is transferred to 2000° C. for sintering for 1 hour, and then ground to a particle size of 150 mesh after cooling to room temperature to obtain the modified white corundum;

[0049] S2: The surface of the green body is purged with nitrogen at a flow rate of 10 m / s, and glaze E is poured on the surface of the green body by pouring glaze method. The parameters of the pouring glaze method are as follows: pouring distance of 35 cm, glaze amount of 60 g / piece, and the size of the brick is 300*600 mm. After the glazing is completed, the green body F is obtained by standing and drying.

[0050] S3: placing the body F in a kiln for firing at a kiln temperature of 2200°C and a firing cycle of 70 minutes, cooling to room temperature after firing, and polishing. The polishing parameters are: first, grinding with a 500-mesh grinding head for 0.5 h, then grinding with a 1000-mesh grinding head for 0.5 h, and finally grinding with a 2000-mesh grinding head for 1 h, to obtain a body G;

[0051] S4: spraying a layer of wear-resistant coating on the surface of the body G, the spraying parameters are spraying distance 60 mm, spraying rate 50 mm / s, to obtain the wear-resistant dual-purpose ceramic glaze;

[0052] The preparation method of the coating used for the wear-resistant coating in S4 is as follows:

[0053] Fluorosilicone resin was dissolved in isopropyl acetate to obtain a mixed solution with a mass fraction of 60%, 0.5wt% of nano silicon dioxide was added, and the mixture was ground at a rotation speed of 400 r / min for 2 hours to obtain a coating for the wear-resistant coating.

[0054] Example 2

[0055] The preparation method of the ceramic glaze in this embodiment is as follows:

[0056] S1: Put the ingredients of the glaze into a ball mill according to the formula ratio 2, the speed of the ball mill is 300r / min, after grinding for 1h, add 20wt% of water, 10wt% of ethylene glycol, 0.5wt% of calcium oxide and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, and use a magnetic iron remover to remove iron, to obtain glaze E;

[0057] The preparation method of modified white corundum in this embodiment is as follows:

[0058] S1.1: Mix chromium nitrate and nano-titanium dioxide in a mass ratio of 3:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 0.5 h, and a mixture A is obtained;

[0059] S1.2: calcining mixture A at 400°C for 2h to obtain composite oxide B, mixing composite oxide B and white corundum in a mass ratio of 1:2, adding 0.2wt% of lanthanum oxide and 0.1wt% of polyethylene glycol 2000, and grinding in a ball mill at a speed of 300r / min for 0.5h to obtain mixture C;

[0060] S1.3: Use a 10% sodium hydroxide solution at room temperature to alkali-wash the mixture C, then immerse the alkali-washed mixture in a silane coupling agent KH-560, stir at a speed of 150 r / min, and heat to 60°C at a rate of 3°C / min while stirring. After keeping the temperature constant for 1 hour, put it in a 110°C oven and dry it for 12 hours to obtain a mixture D;

[0061] S1.4: The mixture D is transferred to 2000° C. for sintering for 1 hour, and then ground to a particle size of 150 mesh after cooling to room temperature to obtain the modified white corundum;

[0062] S2: The surface of the green body is purged with nitrogen at a flow rate of 10 m / s, and glaze E is poured on the surface of the green body by pouring glaze method. The parameters of the pouring glaze method are as follows: pouring distance of 35 cm, glaze amount of 60 g / piece, and the size of the brick is 300*600 mm. After the glazing is completed, the green body F is obtained by standing and drying.

[0063] S3: placing the body F in a kiln for firing at a kiln temperature of 2200°C and a firing cycle of 70 minutes, cooling to room temperature after firing, and polishing. The polishing parameters are: first, grinding with a 500-mesh grinding head for 0.5 h, then grinding with a 1000-mesh grinding head for 0.5 h, and finally grinding with a 2000-mesh grinding head for 1 h, to obtain a body G;

[0064] S4: spraying a layer of wear-resistant coating on the surface of the body G, the spraying parameters are spraying distance 60 mm, spraying rate 50 mm / s, to obtain the wear-resistant dual-purpose ceramic glaze.

[0065] The preparation method of the coating used for the wear-resistant coating in S4 is as follows:

[0066] Fluorosilicone resin was dissolved in isopropyl acetate to obtain a mixed solution with a mass fraction of 60%, 0.5wt% of nano silicon dioxide was added, and the mixture was ground at a rotation speed of 400 r / min for 2 hours to obtain a coating for the wear-resistant coating.

[0067] Example 3

[0068] The preparation method of the ceramic glaze in this embodiment is as follows:

[0069] S1: Put the ingredients of the glaze into a ball mill according to the formula ratio 3, the speed of the ball mill is 300r / min, after grinding for 1h, add 20wt% of water, 10wt% of ethylene glycol, 0.5wt% of calcium oxide and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, and use a magnetic iron remover to remove iron, to obtain glaze E;

[0070] The preparation method of modified white corundum in this embodiment is as follows:

[0071] S1.1: Mix chromium nitrate and nano-titanium dioxide in a mass ratio of 4:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 0.5 h, and a mixture A is obtained;

[0072] S1.2: calcining mixture A at 400°C for 3h to obtain composite oxide B, mixing composite oxide B and white corundum in a mass ratio of 1:4, adding 0.2wt% praseodymium oxide and 0.1wt% polyethylene glycol 2000, and grinding in a ball mill at a speed of 300r / min for 0.5h to obtain mixture C;

[0073] S1.3: Use a 10% potassium hydroxide solution at room temperature to alkali-wash the mixture C, then immerse the alkali-washed mixture in a silane coupling agent KH-792, stir at a speed of 150 r / min, and heat to 60°C at a rate of 3°C / min while stirring. After keeping the temperature constant for 1 hour, put it in an oven at 110°C and dry it for 12 hours to obtain a mixture D;

[0074] S1.4: The mixture D is transferred to 2000° C. for sintering for 1 hour, and then ground to a particle size of 150 mesh after cooling to room temperature to obtain the modified white corundum;

[0075] S2: The surface of the green body is purged with nitrogen at a flow rate of 10 m / s, and glaze E is poured on the surface of the green body by pouring glaze method. The parameters of the pouring glaze method are as follows: pouring distance of 35 cm, glaze amount of 60 g / piece, and the size of the brick is 300*600 mm. After the glazing is completed, the green body F is obtained by standing and drying.

[0076] S3: placing the body F in a kiln for firing at a kiln temperature of 2200°C and a firing cycle of 70 minutes, cooling to room temperature after firing, and polishing. The polishing parameters are: first, grinding with a 500-mesh grinding head for 0.5 h, then grinding with a 1000-mesh grinding head for 0.5 h, and finally grinding with a 2000-mesh grinding head for 1 h, to obtain a body G;

[0077] S4: spraying a layer of wear-resistant coating on the surface of the body G, the spraying parameters are spraying distance 60 mm, spraying rate 50 mm / s, to obtain the wear-resistant dual-purpose ceramic glaze.

[0078] The preparation method of the coating used for the wear-resistant coating in S4 is as follows:

[0079] Fluorosilicone resin was dissolved in isopropyl acetate to obtain a mixed solution with a mass fraction of 60%, 0.5wt% of nano silicon dioxide was added, and the mixture was ground at a rotation speed of 400 r / min for 2 hours to obtain a coating for the wear-resistant coating.

[0080] Example 4

[0081] The preparation method of the ceramic glaze in this embodiment is as follows:

[0082] S1: Put the ingredients of the glaze into a ball mill according to the formula ratio 4, the speed of the ball mill is 300r / min, after grinding for 1h, add 20wt% of water, 10wt% of ethylene glycol, 0.5wt% of calcium oxide and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, and use a magnetic iron remover to remove iron, to obtain glaze E;

[0083] The preparation method of modified white corundum in this embodiment is as follows:

[0084] S1.1: Mix chromium nitrate and nano-titanium dioxide in a mass ratio of 1:1, put them into a ball mill for grinding, the ball mill speed is 300 r / min, the grinding time is 0.5 h, and a mixture A is obtained;

[0085] S1.2: calcining mixture A at 300°C for 2h to obtain composite oxide B, mixing composite oxide B and white corundum in a mass ratio of 1:4, adding 0.2wt% of cerium oxide and 0.1wt% of polyethylene glycol 2000, and grinding in a ball mill at a speed of 300r / min for 0.5h to obtain mixture C;

[0086] S1.3: Use 10% ammonia water at room temperature to perform alkali washing on the mixture C, then immerse the mixture after alkali washing in silane coupling agent KH-560, stir at a speed of 150 r / min, and heat to 60°C at a rate of 3°C / min while stirring. After keeping the temperature constant for 1 hour, put it in an oven at 110°C and dry it for 12 hours to obtain a mixture D;

[0087] S1.4: The mixture D is transferred to 2000° C. for sintering for 1 hour, and then ground to a particle size of 150 mesh after cooling to room temperature to obtain the modified white corundum;

[0088] S2: The surface of the green body is purged with nitrogen at a flow rate of 10 m / s, and glaze E is poured on the surface of the green body by pouring glaze method. The parameters of the pouring glaze method are as follows: pouring distance of 35 cm, glaze amount of 60 g / piece, and the size of the brick is 300*600 mm. After the glazing is completed, the green body F is obtained by standing and drying.

[0089] S3: placing the body F in a kiln for firing at a kiln temperature of 2200°C and a firing cycle of 70 minutes, cooling to room temperature after firing, and polishing. The polishing parameters are: first, grinding with a 500-mesh grinding head for 0.5 h, then grinding with a 1000-mesh grinding head for 0.5 h, and finally grinding with a 2000-mesh grinding head for 1 h, to obtain a body G;

[0090] S4: spraying a layer of wear-resistant coating on the surface of the body G, the spraying parameters are spraying distance 60 mm, spraying rate 50 mm / s, to obtain the wear-resistant dual-purpose ceramic glaze.

[0091] The preparation method of the coating used for the wear-resistant coating in S4 is as follows:

[0092] Fluorosilicone resin was dissolved in isopropyl acetate to obtain a mixed solution with a mass fraction of 60%, 0.5wt% of nano silicon dioxide was added, and the mixture was ground at a rotation speed of 400 r / min for 2 hours to obtain a coating for the wear-resistant coating.

[0093] Comparative Example 1

[0094] In this comparative example, the white corundum was not modified, and the remaining steps were consistent with those in Example 1.

[0095] Comparative Example 2

[0096] In this comparative example, chromium nitrate was not added during the modification process of white corundum, and the remaining steps were consistent with those of Example 1.

[0097] Comparative Example 3

[0098] In this comparative example, nano titanium dioxide is not added during the modification process of white corundum, and the remaining steps are consistent with those of Example 1.

[0099] Comparative Example 4

[0100] In this comparative example, no rare earth oxide is added during the modification process of white corundum, and the remaining steps are consistent with those of Example 1.

[0101] Comparative Example 5

[0102] In this comparative example, silane coupling agent KH-560 is not added during the modification process of white corundum, and the remaining steps are consistent with Example 1.

[0103] Comparative Example 6

[0104] In this comparative example, a wear-resistant coating is not sprayed on the surface of the blank G, and the remaining steps are consistent with those of Example 1.

[0105] The wear resistance of the wear-resistant dual-purpose ceramic glaze prepared in the embodiment and the comparative example was tested according to GB / T 3810.7-2016, the surface stain resistance was tested according to GB / T 3810.14-2016, and the glossiness of the ceramic glaze surface was tested by a gloss meter according to GB / T 11420-2024. The experimental results are summarized in the following table.

[0106] Wear resistance (level) Stain resistance (level) Glossiness(%) Example 1 5 5 90 Example 2 5 5 85 Example 3 5 5 85 Example 4 5 5 85 Comparative Example 1 2 3 75 Comparative Example 2 3 4 80 Comparative Example 3 4 3 80 Comparative Example 4 3 4 80 Comparative Example 5 4 2 70 Comparative Example 6 2 3 70

[0107] Experimental data show that the modification of white corundum and the addition of a wear-resistant layer have improved the wear resistance, stain resistance and glossiness of the ceramic glaze.

[0108] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a wear-resistant dual-purpose ceramic glaze, characterized in that: The preparation method of the wear-resistant dual-purpose ceramic glaze is as follows: S1: Put the glaze ingredients into a ball mill according to the formula ratio, the speed of the ball mill is 300r / min, after grinding for 1h, add 20wt% of water, 10wt% of ethylene glycol, 0.5wt% of calcium oxide and 0.45wt% of sodium tripolyphosphate, increase the speed of the ball mill to 400r / min, continue grinding for 8h, use a magnetic iron remover to remove iron, and obtain glaze E; The formula of the glaze composition is as follows by mass percentage: modified white corundum 25-30%, quartz 20-25%, petalite 20-25%, kaolin 10-15%, silicon carbide 10-15%, and boron carbide 5-10%; The preparation method of modified white corundum is as follows: S1.1: Mix chromium nitrate and nano-titanium dioxide in a mass ratio of (1-3):1, put them into a ball mill for grinding, the ball mill speed is 300r / min, the grinding time is 0.5h, and a mixture A is obtained; S1.2: calcining the mixture A at 300-400°C for 2-3h to obtain a composite oxide B, mixing the composite oxide B and white corundum in a mass ratio of 1:(2-4), adding 0.2wt% of rare earth oxide and 0.1wt% of polyethylene glycol 2000, and grinding in a ball mill at a speed of 300r / min for 0.5h to obtain a mixture C; S1.3: Use a 10% alkali solution at room temperature to wash the mixture C, then immerse the washed mixture in a silane coupling agent, stir at a speed of 150 r / min, and heat to 60°C at a rate of 3°C / min while stirring. After keeping the temperature constant for 1 hour, put it in a 110°C oven and dry it for 12 hours to obtain a mixture D; S1.4: The mixture D is transferred to 2000° C. for sintering for 1 hour, and then ground to a particle size of 150 mesh after cooling to room temperature to obtain the modified white corundum; S2: The surface of the green body is purged with nitrogen, and glaze E is poured on the surface of the green body by a pouring glaze method. After the pouring glaze is completed, the green body is left to dry to obtain a green body F; S3: placing the green body F in a kiln for firing at a kiln temperature of 2200°C and a firing cycle of 70 minutes, cooling to room temperature after firing, and polishing to obtain green body G; S4: spraying a layer of wear-resistant coating on the surface of the body G to obtain the wear-resistant dual-purpose ceramic glaze.

2. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The rare earth oxide in S1.2 is one or more of cerium oxide, lanthanum oxide and praseodymium oxide.

3. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The alkaline solution in S1.3 is one of ammonia water, sodium hydroxide solution and potassium hydroxide solution.

4. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The silane coupling agent in S1.3 is one of silane coupling agent KH-560 and silane coupling agent KH-792.

5. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The flow rate of nitrogen in the S2 is 10 m / s.

6. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The parameters of the glazing method in S2 are: pouring distance 35 cm, glazing amount 60 g / piece, and brick size 300*600 mm.

7. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The polishing parameters in S3 are: first, polishing with a 500-mesh grinding head for 0.5 h, then polishing with a 1000-mesh grinding head for 0.5 h, and finally polishing with a 2000-mesh grinding head for 1 h.

8. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The preparation method of the coating used for the S4 wear-resistant coating is as follows: dissolving fluorosilicone resin in isopropyl acetate to obtain a mixed solution with a mass fraction of 60%, adding 0.5wt% nano-silicon dioxide, and grinding at a speed of 400r / min for 2h to obtain the coating used for the wear-resistant coating.

9. The method for preparing a wear-resistant dual-purpose ceramic glaze according to claim 1, characterized in that: The parameters of the S4 spraying are spraying distance 60 mm and spraying rate 50 mm / s.

10. A wear-resistant dual-purpose ceramic glaze prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Raw full-polish glaze with high abrasion resistance and method for preparing raw full-polish glaze

    CN107176790A

  • Fluorosilicone resin / composite modified nano-material hybrid super-amphiphobic coating and preparation technology thereof

    CN107722827A

  • Abrasion-resistant white glaze, wearproof white glaze ceramics prepared through white glaze, and preparing method of wearproof white glaze ceramics

    CN107879625A

  • Aluminum oxide-based abrasive and preparation method thereof

    CN108865063A

  • Wear-resistant and high-hardness ceramic product and preparation method thereof

    CN109608168A

Cited By

  • Recycled ceramic waste residue, ceramic tile blank and preparation method of ceramic tile blank

    CN120208644A

  • Ceramic recycling waste residue, ceramic brick green and preparation method thereof

    CN120208644B